Interpersonal relationships in education : from theory to practice - Zandvliet, David; Brok, Perry den; Mainhard, Tim; Tartwijk, Jan van (Advances in Learning Environments Research, 2014)
This book brings together recent research on interpersonal relationships in education from a variety of perspectives including research from Europe, North America and Australia. The work clearly demonstrates that positive teacher-student relationships can contribute to student learning in classrooms of various types. Productive learning environments are characterized by supportive and warm interactions throughout the class: teacher-student and student-student. Similarly, at the school level, teacher learning thrives when there are positive and mentoring interrelationships among professional colleagues. Work on this book began with a series of formative presentations at the second International Conference on Interpersonal Relationships in Education (ICIRE 2012) held in Vancouver, Canada, an event that included among others, keynote addresses by David Berliner, Andrew Martin and Mieke Brekelmans. Further collaboration and peer review by the editorial team resulted in the collection of original research that this book comprises. The volume (while eclectic) demonstrates how constructive learning environment relationships can be developed and sustained in a variety of settings. Chapter contributions come from a range of fields including educational and social psychology, teacher and school effectiveness research, communication and language studies, and a variety of related fields. Together, they cover the important influence of the relationships of teachers with individual students, relationships among peers, and the relationships between teachers and their professional colleagues.